On the enhanced corrosion resistance of a selective laser melted austenitic stainless steel. (December 2017) - Chao, Qi; Cruz, Victor; Thomas, Sebastian; Birbilis, Nick; Collins, Paul; Taylor, Adam; Hodgson, Peter D.; Fabijanic, Daniel
Abstract: Corrosion of stainless steels, including the austenitic Fe-Cr-Ni alloys, is associated with MnS inclusions that provide local sites for corrosion pits. Much research effort has been focused on the role of MnS in corrosion of conventional (cast and wrought) stainless steel to date, including microanalysis of MnS and the surrounding microchemistry. Herein, it was elucidated that an austenitic stainless steel (type 316L) when manufactured through selective laser melting was able to be produced without MnS inclusions and hence with no accompanying Cr-depletion in the vicinity of MnS, resulting in superior corrosion resistance relative to wrought form. Graphical abstract: